2018
DOI: 10.1002/open.201800105
|View full text |Cite
|
Sign up to set email alerts
|

Lignin‐g‐poly(acrylamide)‐g‐poly(diallyldimethyl‐ ammonium chloride): Synthesis, Characterization and Applications

Abstract: The search for a renewable substitute to petroleum‐based products has fueled increasing research on lignin, an under‐utilized product from pulping processes. In this work, lignin was copolymerized with acrylamide (AM) and diallyldimethylammonium chloride (DADMAC) under acidic conditions with Na2S2O8 as an initiator, generating a cationic water‐soluble lignin‐g‐P(AM)‐g‐P(DADMAC) copolymer. The optimal reaction conditions, using a 5×4 factorial design experiment, were determined to be an AM/DADMAC/lignin molar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…The macronucleus is polyploid at the time of DNA rearrangements and potentially can generate multiple mating-type gene pairs within a single nucleus if rearrangement occurs independently in each chromatid. The proportions of these gene pairs in a nucleus could be skewed if the process was not entirely random, as suggested before, possibly through a hypothetical “intranuclear coordination” [ 18 , 24 , 25 ]. When growth resumed after conjugation, these copies presumably can assort to different sister nuclei due partly to the lack of centromeric function of the macronuclear chromosomes, eventually producing cells with only 1 form of mating-type gene pair in the macronucleus.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The macronucleus is polyploid at the time of DNA rearrangements and potentially can generate multiple mating-type gene pairs within a single nucleus if rearrangement occurs independently in each chromatid. The proportions of these gene pairs in a nucleus could be skewed if the process was not entirely random, as suggested before, possibly through a hypothetical “intranuclear coordination” [ 18 , 24 , 25 ]. When growth resumed after conjugation, these copies presumably can assort to different sister nuclei due partly to the lack of centromeric function of the macronuclear chromosomes, eventually producing cells with only 1 form of mating-type gene pair in the macronucleus.…”
Section: Resultsmentioning
confidence: 98%
“…In selfing cells, we have uncovered 2 types of DNA abnormality: dual normal MTA / MTB gene pairs and/or mis-paired MTA / MTB genes. It has been shown that roughly half of the newly developed macronuclei are heterogeneous, with multiple potentials for mating types [ 24 , 25 ]. The heterogeneity usually consisted of 2 mating types (occasionally 3) as the newly developed macronucleus starts to divide, and the mating type combinations were not entirely random.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, chitosan‐lignin‐acrylamide graft polymer was used as a flocculant exhibiting 99.3% and 67.0% for reactive orange C‐3R and methyl orange dye removals, respectively . Recently, various cationic and anionic lignin polymers with different molecular weights (MW) and charge densities have been introduced as flocculants for altered systems . The polymerization of kraft lignin and METAC induced a lignin polymer with a charge density of 2.93 mmol/g and a molecular weight of 1650 kg/mol as an effective flocculant for dyes .…”
Section: Applicationmentioning
confidence: 99%
“…[73] Recently, various cationic and anionic lignin polymers with different molecular weights (MW) and charge densities have been introduced as flocculants for altered systems. [68,69,71,72,75,81,82,108] The polymerization of kraft lignin and METAC induced a lignin polymer with a charge density of 2.93 mmol/g and a molecular weight of 1650 kg/mol as an effective flocculant for dyes. [70] The polymerization of acrylic acid, AA, and kraft lignin was also successfully carried out.…”
Section: Lignin Polymer Usementioning
confidence: 99%
“…Lignin is one of the main components of biomass . Lignin has primarily been used as a fuel source, but recent studies have shown that it could be converted into several value‐added products .…”
Section: Introductionmentioning
confidence: 99%